2007
DOI: 10.1088/0953-4075/40/12/019
|View full text |Cite
|
Sign up to set email alerts
|

The electron-energy-loss spectra of methane tagged with Lyman-α photons in the range of doubly excited states

Abstract: The doubly excited states of methane produced in electron interaction have been investigated by measuring the electron-energy-loss spectra tagged with Lyman-α photons at 80 eV incident electron energy and electron scattering angles of 12 • and 24 • . The triply differential cross sections at both angles have been put on the same relative scale for the first time as a function of energy loss. It turned out that electron interaction with methane at 80 eV incident electron energy increases double excitation again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…We have shown that the inner-valence excited states and multiply excited states of molecules are well probed by fluorescence photons emitted by fragments produced in the neutral dissociation [5][6][7][8][9][10][11][12][13][14][15][16]. We recently developed a more powerful method, the (γ , 2γ ) method: a pair of fluorescence photons emitted by a pair of neutral fragments produced in the photoexcitation of a molecule are detected in coincidence in order to eliminate the contribution of ionization [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the inner-valence excited states and multiply excited states of molecules are well probed by fluorescence photons emitted by fragments produced in the neutral dissociation [5][6][7][8][9][10][11][12][13][14][15][16]. We recently developed a more powerful method, the (γ , 2γ ) method: a pair of fluorescence photons emitted by a pair of neutral fragments produced in the photoexcitation of a molecule are detected in coincidence in order to eliminate the contribution of ionization [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…These authors found much larger cross sections due to doubly excited states than those expected within the independent electron model. Optically forbidden doubly excited states of CH 4 , NH 3 and H 2 O were investigated by measuring the electron energy loss spectra tagged with the Lyman-α fluorescence [11,[13][14][15]. However, in the energy range higher than the threshold for the production of excited states of the molecular ion, the dissociative ionizations accompanied by fluorescence emissions are possible and the cross section curves are dominated by such dissociative direct ionizations, preventing us from observing higher-lying multiply excited states.…”
Section: Abmentioning
confidence: 99%
“…Because the large contribution of ionization is eliminated from an electron energy-loss spectrum, buried doubly excited peaks appear in the spectrum. Odagiri et al studied the doubly excited states of simple molecules, such as H 2 , D 2 , N 2 , CH 4 and NH 3 using Co-EELS [20][21][22][23][24][25][26][27], measurements of fluorescence cross section and (γ , 2γ ) spectroscopy [28][29][30]. In particular, they greatly contributed to the elucidation of the doubly excited states of molecular hydrogen and found optically forbidden doubly excited states.…”
Section: Introductionmentioning
confidence: 99%